Experimental analysis of solar power plants with the same characteristics installed in four different directions - Cengiz, Can; Esen, Hikmet; Kapicioglu, Abdullah (Springer, 2024)
In this study, the electrical calculations of four 1 MW Solar Power Plants (SPPs) located in four different directions, established in Samsun (41 degrees 17 ' 25 '' North, 36 degrees 20 ' 1 '' East) province, Turkey, were analyzed and compared in terms of various parameters. Daily production data obtained from real SPPs for the years 2021 and 2022 are used in this study. This way, a comprehensive data source was obtained for four directions. Values such as temperature, relative humidity, wind speed, panel direction, panel angle, and pollution were recorded daily and monthly. It has been observed that the factors affecting the production values in the months when the irradiance values decreased were climatic effects. It has been determined that in cases where the main factor is lack of radiation, the sun starts to fall on September 23, which is the angle of arrival to the Earth, and rises on March 21. The situation recorded between these dates is that the production differences between the west and the east did not show any variation. Production differences varied between 30 and 55% between the north and south directions. The most apparent months of the difference are December and January, when the sun's rays are most oblique to the northern hemisphere. The feasibility study of the installation of SPPs for the climate of the Black Sea region in Turkey according to different roof aspects was also carried out prospectively, and the reactions to possible natural events were reported as recommendations.
Keywords: Solar power plants; Directions; Black Sea; Samsun; Angle